Kontroversi Gaya Komunikasi Politik Presiden K.H. Abdurrahman Wahid - Ervina, Angela; Kriyantono, Rachmat; Wulandari, Maulina Pia (MEDIAKOM : Jurnal Ilmu Komunikasi, 2019)
K.H Abdurrahman Wahid is a religious and political figure in Indonesia. As a religious leader Gus Dur was known as the Chair of the PBNU and the great ulama of the descendants of the Banu Hashim. As a politician, Gus Dur is the fourth President of the Republic of Indonesia. Gus Dur's political communication as a religious figure and the President was known to be controversial. The controversial rhetoric of political communication turns out to have a hidden meaning that can be expressed through the study of discourse analysis using the method presented by Teun A. van Dijk. This study uses an interpretive approach with a critical paradigm. The 2001 Presidential Decree became the main focus of the author in expressing the meaning contained in the controversial phenomenon. The results showed that controversial political communication carried out by Gus Dur turned out to save the people from unconstitutional actions. Key words: Political Communication, K.H Abdurrahman Wahid, Critical Discourse Study.